Characterization of Trypanosoma cruzi Sirtuins as Possible Drug Targets for Chagas Disease - Moretti, Nilmar Silvio; Augusto, Leonardo da Silva; Clemente, Tatiana Mordente; Antunes, Raysa Paes Pinto; Yoshida, Nobuko; Torrecilhas, Ana Claudia; Cano, Maria Isabel Nogueira [UNESP]; Schenkman, Sergio (American Society for Microbiology, 2015)
Acetylation of lysine is a major posttranslational modification of proteins and is catalyzed by lysine acetyltransferases, while lysine deacetylases remove acetyl groups. Among the deacetylases, the sirtuins are NAD(+)-dependent enzymes, which modulate gene silencing, DNA damage repair, and several metabolic processes. As sirtuin-specific inhibitors have been proposed as drugs for inhibiting the proliferation of tumor cells, in this study, we investigated the role of these inhibitors in the growth and differentiation of Trypanosoma cruzi, the agent of Chagas disease. We found that the use of salermide during parasite infection prevented growth and initial multiplication after mammalian cell invasion by T. cruzi at concentrations that did not affect host cell viability. In addition, in vivo infection was partially controlled upon administration of salermide. There are two sirtuins in T. cruzi, TcSir2rp1 and TcSir2rp3. By using specific antibodies and cell lines overexpressing the tagged versions of these enzymes, we found that TcSir2rp1 is localized in the cytosol and TcSir2rp3 in the mitochondrion. TcSir2rp1 overexpression acts to impair parasite growth and differentiation, whereas the wild-type version of TcSir2rp3 and not an enzyme mutated in the active site improves both. The effects observed with TcSir2rp3 were fully reverted by adding salermide, which inhibited TcSir2rp3 expressed in Escherichia coli with a 50% inhibitory concentration (IC50) ± standard error of 1 ± 0.5 μM. We concluded that sirtuin inhibitors targeting TcSir2rp3 could be used in Chagas disease chemotherapy.